Examining Subcortical Infarcts in the Era of Acute Multimodality CT Imaging - Tan, Mindy Y. Q.; Singhal, Shaloo; Ma, Henry; Chandra, Ronil V.; Cheong, Jamie; Clissold, Benjamin B.; Ly, John; Srikanth, Velandai; Phan, Thanh G. (Frontiers in Neurology, 2016)
Background: Lacunar infarcts have been characterized as small subcortical infarcts, resulting from “in situ microatheroma or lipohyalinosis” in small vessels. Based on this hypothesis, such infarcts should not be associated with large areas of perfusion deficits extending beyond subcortical regions to involve cortical regions. By contrast, selected small subcortical infarcts, as defined by MR imaging in the subacute or chronic stage, may initially have large perfusion deficits or related large vessel occlusions. These infarcts with ‘lacunar’ phenotype may also be caused by disease in the parent vessel and may have very different stroke mechanisms from small vessel disease. Our aim was to describe differences in imaging characteristics between patients with small subcortical infarction with ‘lacunar phenotype’ from those with lacunar mechanism. Methods: Patients undergoing acute CT Perfusion/angiography (CTP/CTA) within 6 hours of symptom onset and follow-up magnetic resonance imaging (MRI) for ischaemic stroke were included (2009-2013). A lacunar infarct was defined as a single subcortical infarct (SSI) ≤20 mm on follow-up MRI. Presence of perfusion deficits, vessel occlusion and infarct dimensions were compared between lacunar infarcts and other topographical infarct types. Results: Overall, 182 patients (mean age 66.4±15.3 years, 66% male) were included. SSI occurred in 31 (17%) patients. Of these, 12 (39%) patients had a perfusion deficit compared with those with any cortical infarction (120/142, 67%), and the smallest SSI with a perfusion deficit had a diameter of <5mm. The majority of patients with SSI (8/12, 66.7%) had a relevant vessel occlusion. A quarter of SSIs had a large-artery stroke mechanism evident on acute CTP/CTA. Lacunar mechanism was present in 3/8 patients with corona radiata, 5/10 lentiform nucleus, 5/6 posterior limb of internal capsule [PLIC], 3/5 thalamic infarcts and 1/2 miscellaneous locations. There was a trend toward significance with regard to finding a lacunar mechanism among patients with thalamic and PLIC versus lentiform nucleus and corona radiata infarcts (p=0.13). Conclusion: Diverse stroke mechanisms were present among subcortical infarcts in different locations. Whenever available, acute CTP/CTA should be combined with subacute imaging of subcortical infarcts to differentiate the ‘lacunar phenotype’ from subcortical infarcts with lacunar mechanism.